The relationship between passion for coaching and the coaches' interpersonal behaviors: The mediating role of coaches' perception of the relationship quality with athletes. Issue 4 (August 2019) - Kim, Inwoo; Lee, Keunchul; Kang, Sangwook
According to Self-Determination Theory, sports coaches' autonomy-supportive behaviors positively influence athletes' different aspects, such as motivation, well-being, and performance, while controlling behaviors of coaches tend to diminish such variables. Although many researchers agree that autonomy-supportive coaching style should be promoted rather than a controlling style, there is scarce research investigating the antecedents of such behavioral styles. The aim of this study was to examine a model of potential determinants of coaches' interpersonal behaviors by investigating the relationship between passion for coaching and their behavioral styles and verifying the mediating role of coaches' perceived relationship quality with their athletes. A total of 172 coaches participated in the survey, and data sets were analyzed using structural model analysis. Results revealed that coaches' harmonious passion positively predicted autonomy-supportive behaviors but negatively predicted controlling behaviors, and these pathways were mediated by coaches' perception of the relationship with their athletes. The implications for coaches and researchers from those results are discussed.